2017
DOI: 10.1128/iai.00373-17
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbiofilm Formation by Bordetella pertussis Strains Correlates with Enhanced Virulence Traits

Abstract: Pertussis, or whooping cough, caused by the obligate human pathogen is undergoing a worldwide resurgence. The majority of studies of this pathogen are conducted with laboratory-adapted strains which may not be representative of the species as a whole. Biofilm formation by plays an important role in pathogenesis. We conducted a side-by-side comparison of the biofilm-forming abilities of the prototype laboratory strains and the currently circulating isolates from two countries with different vaccination programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 71 publications
3
36
0
2
Order By: Relevance
“…Based on these results, biofilm formation has been proposed by us and others as a possible strategy adopted by B. pertussis to infect, persist and continually circulate in the community (Cattelan et al ., 2016). Consistent with this hypothesis, we found that currently circulating strains from Argentina and USA produce significantly higher levels of biofilms when compared to a laboratory reference strain and colonize the mouse nose and trachea at higher numbers than the prototype laboratory strain (Cattelan et al ., 2017). These results also provide evidence that hyperbiofilm growth is a strategy employed by circulating organisms to infect and survive inside their host.…”
Section: [Background]supporting
confidence: 72%
See 2 more Smart Citations
“…Based on these results, biofilm formation has been proposed by us and others as a possible strategy adopted by B. pertussis to infect, persist and continually circulate in the community (Cattelan et al ., 2016). Consistent with this hypothesis, we found that currently circulating strains from Argentina and USA produce significantly higher levels of biofilms when compared to a laboratory reference strain and colonize the mouse nose and trachea at higher numbers than the prototype laboratory strain (Cattelan et al ., 2017). These results also provide evidence that hyperbiofilm growth is a strategy employed by circulating organisms to infect and survive inside their host.…”
Section: [Background]supporting
confidence: 72%
“…Biofilms of B. pertussis form on a variety of artificial surfaces and under static, shaking, and fluid flow conditions (Mishra et al ., 2005; Sloan et al ., 2007; Serra et al ., 2011). Microscopic evaluation of these biofilms shows that this bacterium produces irregularly shaped microcolonies separated by fluid channels, embedded in an exopolymeric matrix composed by extracellular DNA (eDNA), proteins and polysaccharides (Parise et al ., 2007; Sloan et al ., 2007; Serra et al ., 2008; Conover et al ., 2011; Nicholson et al ., 2012; Ganguly et al ., 2014; Cattelan et al ., 2017). In addition to forming biofilms in the laboratory setting, B. pertussis forms multidimensional organ-adherent biofilms on the nose and trachea during experimental infections of mice.…”
Section: [Background]mentioning
confidence: 99%
See 1 more Smart Citation
“…In both a nose and a trachea model, distinct architectural features adherent to ciliated epithelium were observed; in the form of mats, towers or pillars for B. bronchiseptica, and clusters and macrocolonies for B. pertussis. Furthermore, Cattelan et al observed an association between increased biofilm formation by B. pertussis and higher levels of bacterial colonization in the nose and trachea of mice [183]. Direct observations of B. pertussis biofilm in humans have not been reported, but abundant extracellular Bordetellae were observed in respiratory tissue samples from 15 infants who had died from confirmed B. pertussis pneumonia [184].…”
Section: Pertussis and Other Bordertella Infectionsmentioning
confidence: 99%
“…[6,7] Several major factors contribute to the rise of the pertussis infections.These include that some current circulating B. pertussis strains are deficient in the production of certain vaccine targets resulting in probable escape from vaccine-induced immunity. [8,9] Furthermore,the current acellular vaccine does not prevent infections and the immunity induced can only last ashort time. [10][11][12] Therefore,there is an urgent need for an ew generation of anti-pertussis vaccines.…”
Section: Introductionmentioning
confidence: 99%